Knjižnično informacijsko znanje v tretjem triletju osnovne šole - Bratuša, Alja (Šolska knjižnica, 2012)
Library and information knowledge (LIK) has been part of curriculum in the third triad of primary school for fifteen years. Since this is a demanding and complex process, we show the role of school librarian and teacher in planning, preparation of teaching materials, execution of lessons and evaluation of teaching. In addition we bring attention to the role of school librarian in teaching basic goals of the new LIK curriculum in three key areas: reading, information literacy and learning. The paper concludes with a thought on advantad+ges and weaknesses of the LIK programme in the third triad.
Keywords: knjižnično informacijsko znanje; medpredmetno povezovanje; osnovne šole; šolske knjižnice